The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s10548-011-0204-z
|View full text |Cite
|
Sign up to set email alerts
|

Water Immersion to the Femur Level Affects Cerebral Cortical Activity in Humans: Functional Near-Infrared Spectroscopy Study

Abstract: Water immersion is widely used in physiotherapy and may even improve the functional outcomes of hemiplegic patients after stroke. To investigate the cortical responses to water immersion, functional near-infrared spectroscopy (fNIRS) was used to measure cortical activations in the primary somatosensory area (S1), parietal association area (PAA), supplementary motor area (SMA), and primary motor area (M1). Nine healthy adult males were rested in a sitting position for 15 min with simultaneous measurements of fN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…We have previously shown that whole-body water immersion (WI) increases cutaneous afferent input and leads to a modulation of sensorimotor integration [15]–[17]. However, low-intensity afferent stimuli by whole-body WI did not alter corticospinal excitability or intracortical circuits.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that whole-body water immersion (WI) increases cutaneous afferent input and leads to a modulation of sensorimotor integration [15]–[17]. However, low-intensity afferent stimuli by whole-body WI did not alter corticospinal excitability or intracortical circuits.…”
Section: Introductionmentioning
confidence: 99%
“…This finding suggests that the somatosensory input from water immersion might activate this cortical area [11]. However, to the best of our knowledge, there is no direct evidence that water immersion has any effect on somatosensory cortical processing.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence of interference is typically measured as decreased performance of one, or both, tasks under dual‐task conditions relative to performance on their own (Woollacott and Shumway‐Cook, ). For example, a postural balancing task performed in water might be associated with increased brain activity relative to on land, which is consistent with previous findings for healthy adults (Sato et al ., ). If so, one might hypothesize that more dual‐task interference will be observed when the postural task is performed simultaneously with a non‐motor cognitive task (e.g.…”
mentioning
confidence: 97%